2019
DOI: 10.1038/s41385-018-0123-3
|View full text |Cite
|
Sign up to set email alerts
|

The recruitment of extra-intestinal cells to the injured mucosa promotes healing in radiation enteritis and chemical colitis in a mouse parabiosis model

Abstract: Mucosal healing occurs through migration and proliferation of cells within injured epithelium, yet these processes may be inadequate for mucosal healing after significant injury where the mucosa is denuded. We hypothesize that extra-intestinal cells can contribute to mucosal healing after injury to the small and large intestine. We generated parabiotic pairs between wild-type and tdTomato mice which were then subjected to radiation-induced enteritis and 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced coliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…SuperMApo stimulates wound healing via the pro-healing properties of fibroblasts and IEC. We did not study whether efferocytosis factors also promoted extra-intestinal bone marrow-derived cell recruitment to participate in wound healing, as observed in a recent study using a parabiosis chemical-induced colitis model ( 50 ). It has been shown that colonic fibroblasts are critically involved in tissue repair in the gastrointestinal tract ( 43 ).…”
Section: Discussionmentioning
confidence: 97%
“…SuperMApo stimulates wound healing via the pro-healing properties of fibroblasts and IEC. We did not study whether efferocytosis factors also promoted extra-intestinal bone marrow-derived cell recruitment to participate in wound healing, as observed in a recent study using a parabiosis chemical-induced colitis model ( 50 ). It has been shown that colonic fibroblasts are critically involved in tissue repair in the gastrointestinal tract ( 43 ).…”
Section: Discussionmentioning
confidence: 97%
“…The severity of radiation-induced enteritis was assessed by the degree of maintenance of the epithelial architecture, crypt damage, vascular enlargement, and infiltration of inflammatory cells in the lamina propria. This assessment is a modification of the histological score parameter used by Sung et al [ 29 ]. To perform immunohistochemical analysis, slides were subjected to antigen retrieval and then treated with 0.3% hydrogen peroxide in methyl alcohol for 20 min to block endogenous peroxidase activity.…”
Section: Methodsmentioning
confidence: 99%
“…The severity of radiation-induced enteritis was assessed by the degree of maintenance of the epithelial architecture, crypt damage, vascular enlargement, and in ltration of in ammatory cells in the lamina propria. This assessment is a modi cation of the histological score parameter used by Sung et al [70]. To perform immunohistochemical analysis, slides were subjected to antigen retrieval and then treated with 0.3% hydrogen peroxide in methyl alcohol for 20 min to block endogenous peroxidase activity.…”
Section: Histological Analysis Of the Intestinementioning
confidence: 99%